West African urbanization : a study of voluntary associations in social change - Little, Kenneth Lindsay (Cambridge England : University Press, 1965)
This book is concerned with the study of voluntary associations in W. Africa which have grown up, in urban areas, to satisfy people's needs at a period of social transition between the old traditional society and the impact of the individualistic and industrialised urban areas.
Includes index.
Includes bibliographical references: p. 167-172.
lje 14/05/2018
Loans
Keywords: Urbanization; Urbanization-Africa.